2019
DOI: 10.1101/786426
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulation of Bud Emergence by a MAPK Pathway

Abstract: All cells establish and maintain an axis of polarity that is critical for cell shape and progression through the cell cycle. A well-studied example of polarity establishment is bud emergence in yeast, where the Rho GTPase Cdc42p regulates symmetry breaking at bud sites and the establishment of polarity by interacting with effector proteins. The prevailing view of bud emergence does not account for regulation by extrinsic cues or signal transduction pathways. Here, we show that the MAPK pathway that controls fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 174 publications
0
2
0
Order By: Relevance
“…Given that the fMAPK pathway is induced under nutrient-limiting conditions, one possibility is that derepression of glucose-repressed genes may be required for fMAPK function (Carlson, 1999). In a related study from our lab (Prabhakar et al, 2019), we show that the fMAPK pathway is regulated throughout the cell cycle and peaks in G 2 /M phase. Cell synchronization experiments also showed that the fMAPK pathway is activated (in G 2 /M) to the same levels as the mating and HOG pathways.…”
Section: Cdc42p-dependent Mapk Pathways Show Different Kinetic Profilesmentioning
confidence: 55%
“…Given that the fMAPK pathway is induced under nutrient-limiting conditions, one possibility is that derepression of glucose-repressed genes may be required for fMAPK function (Carlson, 1999). In a related study from our lab (Prabhakar et al, 2019), we show that the fMAPK pathway is regulated throughout the cell cycle and peaks in G 2 /M phase. Cell synchronization experiments also showed that the fMAPK pathway is activated (in G 2 /M) to the same levels as the mating and HOG pathways.…”
Section: Cdc42p-dependent Mapk Pathways Show Different Kinetic Profilesmentioning
confidence: 55%
“…Given that the fMAPK pathway is induced under nutrient-limiting conditions, one possibility is that derepression of glucose-repressed genes ( 138 ) may be required for fMAPK function. In a related study from our lab ( 139 ), we show that the fMAPK pathway is regulated throughout the cell cycle and peaks in G 2 /M phase. Cell synchronization experiments also showed that the fMAPK pathway is activated (in G 2 /M) to the same levels as the mating and HOG pathways.…”
Section: Discussionmentioning
confidence: 63%